2019
DOI: 10.1128/aac.00996-19
|View full text |Cite
|
Sign up to set email alerts
|

NU-6027 Inhibits Growth of Mycobacterium tuberculosis by Targeting Protein Kinase D and Protein Kinase G

Abstract: Tuberculosis (TB) is a global health concern, and this situation has further worsened due to the emergence of drug-resistant strains and the failure of BCG vaccine to impart protection. There is an imperative need to develop highly sensitive, specific diagnostic tools, novel therapeutics, and vaccines for the eradication of TB. In the present study, a chemical screen of a pharmacologically active compound library was performed to identify antimycobacterial compounds. The phenotypic screen identified a few nove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 86 publications
1
26
0
Order By: Relevance
“…SAR studies revealed that the nitroso group is important for anti-tubercular activity associated with this series. In concordance previous studies have also shown that nitro or nitroso functional groups are essential for the anti-tubercular activity of small molecules (Singh et al, 2008;Kidwai et al, 2017Kidwai et al, , 2019. We also show that substitution at the para-position of the phenyl ring with either electron withdrawing group such as (chloro and cyano) or electron donating groups (such as methyl) improved NSC 18725 activity in vitro.…”
Section: Discussionsupporting
confidence: 91%
“…SAR studies revealed that the nitroso group is important for anti-tubercular activity associated with this series. In concordance previous studies have also shown that nitro or nitroso functional groups are essential for the anti-tubercular activity of small molecules (Singh et al, 2008;Kidwai et al, 2017Kidwai et al, , 2019. We also show that substitution at the para-position of the phenyl ring with either electron withdrawing group such as (chloro and cyano) or electron donating groups (such as methyl) improved NSC 18725 activity in vitro.…”
Section: Discussionsupporting
confidence: 91%
“…Some host-targeting compounds have been demonstrated to possess activity against bacterial kinases, such as the cyclin-dependent kinase 1 inhibitor NU-6027 ( Kidwai et al, 2019 ) and the CHK1 inhibitor AZD7762 ( Kanehiro et al, 2018 ), which inhibit the M.tb kinase, PknG. To examine if DDUG can inhibit bacterial growth in broth, disk diffusion and resazurin assays were conducted, examining a range of pathogenic bacteria and M.tb ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…The activity of DDUG against M.tb in broth at concentrations similar to those achieved intracellularly suggests an alternative, CHK2-independent mode of activity. Similarly, the activity of DDUG against some bacteria further suggest DDUG might have promiscuous activity on bacterial kinases, similar to NU-6027 (Kidwai et al, 2019) and AZD7762 (Kanehiro et al, 2018), or otherwise be toxic due to physical properties such as crystallization if concentrated by the macrophage. Conversely, DDUG is not active against M.tb's close family members, M. abscessus and M. bovis-BCG, or Salmonella, which it did inhibit in macrophages, and is active against a small array of seemingly unrelated bacteria ( Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…PknG also regulates the redox homeostatic system by phosphorylation of ribosomal protein L13, which then binds to RenU, a nucleoside diphosphatelinked moiety X (nudix) hydrolase, promoting hydrolysis of FAD, ADP-ribose, and NADH [48]. Since oxidative stress and antibiotic resistance are closely linked, particularly for INH and ETH, it provides a possible link of PknG being involved in drug resistance [48][49][50].…”
Section: Ser/thr/tyr Phosphorylationmentioning
confidence: 99%